The Effectiveness of Legal Aid Offices in Ensuring the Rights of Defendants in Court - Maria Waas; Sherly Adam; Hadibah Zachra Wadjo (Interdisciplinary Journal of Advanced Research and Innovation, 2026)
The implementation of the Legal Aid Post (Pos Bantuan Hukum or Posbakum) at the Ambon District Court represents the fulfillment of every citizen's constitutional right to legal assistance a right grounded in the principles of the rule of law, equality before the law, and access to justice. This research aims to analyze the effectiveness of the Legal Aid Post in fulfilling defendants' rights to legal assistance and to examine the factors influencing its implementation. This is an empirical legal study employing statutory, conceptual, and sociological approaches. Data were gathered through both library and field research and analyzed using a descriptive-qualitative method. The findings indicate that the Legal Aid Post at the Ambon District Court has played a role in providing legal consultation, drafting legal documents, and facilitating legal representation for indigent defendants. However, its implementation has not been optimal due to resource limitations, low public legal awareness, and administrative obstacles in the provision of legal aid. Therefore, it is necessary to strengthen the Legal Aid Post institutionally, improve service quality, and foster synergy among the court, legal aid organizations, and law enforcement agencies to ensure that defendants' rights to legal assistance are fulfilled effectively, fairly, and with legal certainty.